Revision of marine genera Clitellio and Clitelloides (Oligochaeta Tubificidae) with description of a new species from the East-Siberean Sea (in Russian) - Finogenova, N.P. (Zoologicheskii Zhurnal, 1991)
Reviewed are the genera Clitellio and Clitelloides. Genus Clitellio is divided into two subgenera: Clitellio Savigny with single-pointed and bifid setae, the atria approximately equal in length vas deferens, weakly developed muscles on the gonoduct and Clitelloides (Finogenova) rank. n. with bifid setae, the atria much longer (2 to 4 times) vas deferens and with a powerful layer of muscles along the entire length of the gonoduct. The subgenus Clitellio includes C arenarius (Muller) and C saxosus Finogenova. The subgenus Clitelloides includes C poseidonicus (Finogenova) and C orientalis sp. n. with setae with the upper tooth equal, a bit longer or shorter than the lower one, with the vas deferens proximally narrow, thin-walled, distally wide and thick walled, glandular atra wide, soft penis normally located.